Are Enslaved Children Called to Come to Jesus?: Freeborn and Enslaved Children in John Chrysostom’s On Vainglory - Martens, John W. (Biblical interpretation, 2020)
John Chrysostom, circa 349–407 ce , wrote “On Vainglory, or The Right Way to Raise Children,” which purports to be about raising all Christian children. In fact, out of ninety chapters, only one deals with girls. Even more significant are the numerous overlooked children in the text, who are present but whose Christian education is never discussed because they are enslaved. This paper utilizes childist criticism to draw these enslaved children from hiddenness into plain sight. The paper is situated in the context of Jesus’ teaching about children because Chrysostom believes that the best way to raise children is by teaching them stories from the Bible, Hebrew Bible first, then New Testament, but instead of an openness to all children he discusses only freeborn, elite boys. Chrysostom’s treatise exposes the context of how few children in late antiquity could be shaped by biblical interpretation intended for all children. (147 words)